INORGANIC PYROPHOSPHATE CONTENT AND METABOLITES IN POTATO AND TOBACCO PLANTS EXPRESSING ESCHERICHIA-COLI PYROPHOSPHATASE IN THEIR CYTOSOL - Sonnewald, Uwe; et al. (Planta, 1992)
Metabolite levels and carbohydrates were investigated in the leaves of tobacco (Nicoliana tabacum L.) and leaves and tubers of potato (Solanum tuberosum L.) plants which had been transformed with pyrophosphatase from Escherichia coli. In tobacco the leaves contained two- to threefold less pyrophosphate than controls and showed a large increase in UDP-glucose, relative to hexose phosphate. There was a large accumulation of sucrose, hexoses and starch, but the soluble sugars increased more than starch. Growth of the stem and roots was inhibited and starch, sucrose and hexoses accumulated. In potato, the leaves contained two- to threefold less pyrophosphate and an increased UDP-glucose/hexose-phosphate ratio. Sucrose increased and starch decreased. The plants produced a larger number of smaller tubers which contained more sucrose and less starch. The tubers contained threefold higher UDP-glucose, threefold lower hexose-phosphates, glycerate-3-phosphate and phosphoenolpyruvate, and up to six-fold more fructose-2,6-bisphosphatase than the wild-type tubers. It is concluded that removal of pyrophosphate from the cytosol inhibits plant growth. It is discussed how these results provide evidence that sucrose mobilisation via sucrose synthase provides one key site at which pyrophosphate is needed for plant growth, but is certainly not the only site at which pyrophosphate plays a crucial role.
Keywords: INORGANIC PYROPHOSPHATE; NICOTIANA; SINK-SOURCE; SOLANUM; SUCROSE METABOLISM; TRANSGENIC PLANTS